2017
DOI: 10.3389/fneur.2017.00078
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Neuraminidase Induces a Moderate and Transient Myelin Vacuolation Independent of Complement System Activation

Abstract: AimsSome central nervous system pathogens express neuraminidase (NA) on their surfaces. In the rat brain, a single intracerebroventricular (ICV) injection of NA induces myelin vacuolation in axonal tracts. Here, we explore the nature, the time course, and the role of the complement system in this damage.MethodsThe spatiotemporal analysis of myelin vacuolation was performed by optical and electron microscopy. Myelin basic protein-positive area and oligodendrocyte transcription factor (Olig2)-positive cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Microglial cells morphology was analyzed using FIJI free software (http://fiji.sc/Fiji). A comprehensive explanation of the procedure is available elsewhere (Fernández-Arjona et al, 2017). Briefly, the TIFF image was subjected to RGB channel separation, and the blue channel was chosen for the analysis (as the brown color from oxidized diaminobenzidine is enhanced in this channel).…”
Section: Morphological Analysis Of Microglial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microglial cells morphology was analyzed using FIJI free software (http://fiji.sc/Fiji). A comprehensive explanation of the procedure is available elsewhere (Fernández-Arjona et al, 2017). Briefly, the TIFF image was subjected to RGB channel separation, and the blue channel was chosen for the analysis (as the brown color from oxidized diaminobenzidine is enhanced in this channel).…”
Section: Morphological Analysis Of Microglial Cellsmentioning
confidence: 99%
“…Various aspects of NA-induced inflammation have been described during the previous years (Fernandez-Arjona et al, 2019a;Fernandez-Arjona et al, 2021;Granados-Durán et al, 2015;Granados-Durán et al, 2016;Granados-Durán et al, 2017). For instance, NA is able to activate microglial cells acting primarily through the pattern receptor toll-like receptor 4 (TLR4) (Fernandez-Arjona et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, NA itself can induce the activation of the complement system, which is present in the cerebrospinal fluid [31]. Other damages provoked by NA in the CNS include myelin vacuolation, ependymal denudation, ventriculomegaly, and eventually hydrocephalus [27, 28, 32]. The wide range of effects of NA within the CNS makes it worth to explore its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, biallelic mutations in the NANS gene, 73 which impairs endogenous Neu5Ac synthesis, have been linked to prenatal hydrocephalus and demyelination. 60 , 74 Experimental studies have shown that low‐dose neuraminidase‐induced astrogliosis and demyelination, 75 , 76 while high‐dose neuraminidase‐induced hydrocephalus in rats. 21 However, there is currently no commercialized pharmacological intervention available to reduce brain Neu5Ac in animal models.…”
Section: Discussionmentioning
confidence: 99%